2006
DOI: 10.3104/perspectives.316
|View full text |Cite
|
Sign up to set email alerts
|

Addressing challenging behaviour in children with Down syndrome: The use of applied behaviour analysis for assessment and intervention

Abstract: -Children with Down syndrome are at an increased risk for engaging in challenging behaviour that may be part of a behavioural phenotype characteristic of Down syndrome. The methodology of applied behaviour analysis has been demonstrated effective with a wide range of challenging behaviours, across various disabilities. Applications to children with Down syndrome and the examination of behaviourally based strategies to specifically address the unique characteristics of children with Down syndrome are limited. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…1991). Not only are children with Down syndrome more likely to show higher rates of behavioural problems than non‐disabled children, these behaviours tend to have characteristics specific to the syndrome, the Down syndrome behavioural phenotype (Feeley & Jones 2006; Fidler et al . 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1991). Not only are children with Down syndrome more likely to show higher rates of behavioural problems than non‐disabled children, these behaviours tend to have characteristics specific to the syndrome, the Down syndrome behavioural phenotype (Feeley & Jones 2006; Fidler et al . 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such behaviors often affect academic progress, classroom placement, social acceptance and adaptive function. 4,5,28 To our knowledge, there have been no pharmacologic trials in children with Down syndrome þ ADHD. Overall, our subjects manifest a range of intellectual disability (mild-severe), making our sample representative of many children with Down syndrome residing in the community.…”
Section: Discussionmentioning
confidence: 99%
“…3 In children with Down syndrome and intellectual disability, these comorbidities and other adaptive impairments makes the approach to management multimodal. 4,5 In neurobiologic terms, ADHD has been linked to dysmaturation of prefrontal-subcortical regions and/or neurochemical dysfunction in associated circuits. 6,7 Disturbances in catecholamine neurotransmission, primarily dopamine and norepinephrine, figure prominently in understanding the salient cognitive and behavioral symptoms.…”
mentioning
confidence: 99%
“…It has been suggested in the literature that, by comparison with children with other aetiologies of similar intellectual impairment, young children with DS show social strengths (Fidler et al . ), although other research has documented deficits in core aspects of interpersonal functioning in DS (Feeley & Jones, ; Wishart , ). For instance, several studies have shown that children with DS tend to divert attention from challenging tasks or opt out of learning opportunities by over‐engaging in social interactive behaviours (Wishart ; Kasari & Freeman ; Cebula et al .…”
mentioning
confidence: 95%
“…Clinical, research and parental reports have described a 'prototypical' personality profile of children with DS, marked by enhanced sociability and social attention, generally positive mood and cheerful disposition (Wishart & Johnston 1990;Dykens et al 2006). It has been suggested in the literature that, by comparison with children with other aetiologies of similar intellectual impairment, young children with DS show social strengths (Fidler et al 2008), although other research has documented deficits in core aspects of interpersonal functioning in DS (Feeley & Jones, 2006;Wishart 1993Wishart , 2007. For instance, several studies have shown that children with DS tend to divert attention from challenging tasks or opt out of learning opportunities by overengaging in social interactive behaviours (Wishart 1993;Kasari & Freeman 2001;Cebula et al 2010).…”
mentioning
confidence: 99%